Adverse events and mortality: comparative analysis between diagnostic and interventional endoscopic ultrasound. (2nd August 2020) - Marchetti, Giulia; Ricardo, Vítor Doria; Ardengh, André Orsini; de Almeida, Arthur Ferraz; Taglieri, Eloy; Micelli-Neto, Otávio; Kemp, Rafael; dos Santos, José Sebastião; Ardengh, José Celso
Abstract: Background and aims: Escalating an indication of EUS for diagnosis and treatment justifies the evaluation of the conditions associated with the adverse events (AE) and related deaths. The aim is to evaluate and compare the incidence of AE and deaths after diagnostic-EUS (D-EUS) and interventional-EUS (I-EUS). Methods: This retrospective study included patients undergoing D-EUS and I-EUS, in two centers for 28 years (03/1992 to 12/2019). Were noted parameters such as: age, gender, indication of EUS, modality, time of occurrence and severity of AE, type of treatment imposed and whether there was death. Descriptive analysis was performed using means, standard deviation and frequencies of the variables of interest. Results: 13, 196 procedures performed, 9843 D-EUS and 3353 I-EUS. Thirty-seven (0.3%) had AE with six deaths (0.04%). The overall rate of AE for D-EUS and I-EUS was 0.08% and 0.86%, respectively ( p > .05). Three deaths (0.03%) occurred after D-EUS and three (0.09%) after I-EUS. AE were immediate and early in 70% and 30%, respectively, with no late complications. Perforation was detected immediately in 80% and early in 20%, being more frequent after D-EUS than I-EUS. Acute pancreatitis occurred immediately in 70% and early in 30%. The AE were mild, moderate, and severe in 35.1%, 27%, and 37.8%, respectively. Overall, D-EUS presented the majority of AE as severe (87.5%), while I-EUS presented mild AE in most cases (41.4%), followed by severe complications (24.1%). Conclusions: Despite the low incidence of AE and mortality after EUS, the occurrence of severe complications, especially perforation in D-EUS, may support the review of therapeutic protocols, aiming to ensure that a quality and safety process is implemented in the practice of EUS.